Forms and significance of the prenatal “attachment” for the mother and the child - Velemínský, Miloš; Velemínský, Miloš; Šimečková, Alžběta (Journal of Nursing, Social Studies and Public Health, 2018)
Prenatal psychology searches for answers to how a mother's behaviour and reactions affect the psychological condition of her child. The goal of this article is focused on the significance and forms of the prenatal attachment and the ways of their realization. We used the method of content analysis of domestic and foreign documents. The data shows a close relationship between the prenatal and postnatal attachment. The relationship is based on emotional, tactile, vocal and sound, visual and auditory communication. The quality of the attachment is affected by a number of factors, such as a non-functional partnership, the relationship towards the expected child, the woman's social situation and her total familiar psychosocial situation. There is evidence of the relationship between the prenatal bonding and the occurrence of depression in the woman. This data emphasizes the significance of the attachment. Studies show the influence of the prenatal attachment on the quality of the postnatal attachment.
Keywords: Nonverbal Communication; vývoj plodu; Placenta; neverbální komunikace; lidé; poporodní deprese; Depression, Postpartum; Maternal-Fetal Relations; matky; maternofetální vztahy; Fetal Development; placenta; těhotenství; Pregnancy; Mothers; Object Attachment; připoutání k objektu; Humans